2013
DOI: 10.1080/09540121.2012.749332
|View full text |Cite
|
Sign up to set email alerts
|

Routine HIV counseling and testing during antenatal care in Ukraine: A qualitative study of the experiences and perspectives of pregnant women and antenatal care providers

Abstract: Ukraine has one of the highest levels of HIV prevalence in Europe. Provider-initiated HIV testing and counseling (PITC) is routine during antenatal care (ANC) in Ukraine, with nearly all pregnant women receiving HIV testing. National policies state that testing is voluntary, with consent and confidentiality protections, but little is known about actual testing implementation and adherence to these policies. A qualitative study was conducted to explore women's and providers' experiences of HIV testing during AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…A recent qualitative study of pregnant women in Ukraine highlighted concerns about inadvertent disclosure of a woman's HIV status to other patients in a healthcare setting (and the possibility of this leading to community disclosure), as well as "moral pressure" from clinical staff to disclose HIV status to sexual partners and medical staff (54). Although not practically implemented, there is a legal obligation for HIV-positive people in Ukraine to inform sexual partners of their HIV status, which raises concerns around criminalisation of non-disclosure among patients including pregnant women (54). Healthcare providers reported lack of time and skills to conduct post-test counselling and a need for psychologists to support them in this, but none of the women who received a psychological referral had taken this up (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent qualitative study of pregnant women in Ukraine highlighted concerns about inadvertent disclosure of a woman's HIV status to other patients in a healthcare setting (and the possibility of this leading to community disclosure), as well as "moral pressure" from clinical staff to disclose HIV status to sexual partners and medical staff (54). Although not practically implemented, there is a legal obligation for HIV-positive people in Ukraine to inform sexual partners of their HIV status, which raises concerns around criminalisation of non-disclosure among patients including pregnant women (54). Healthcare providers reported lack of time and skills to conduct post-test counselling and a need for psychologists to support them in this, but none of the women who received a psychological referral had taken this up (54).…”
Section: Discussionmentioning
confidence: 99%
“…Although not practically implemented, there is a legal obligation for HIV-positive people in Ukraine to inform sexual partners of their HIV status, which raises concerns around criminalisation of non-disclosure among patients including pregnant women (54). Healthcare providers reported lack of time and skills to conduct post-test counselling and a need for psychologists to support them in this, but none of the women who received a psychological referral had taken this up (54). This may partly reflect the fact that mental health services are widely stigmatised in Ukraine (55).…”
Section: Discussionmentioning
confidence: 99%
“…1 Nearly all pregnant women in Ukraine receive HIV testing as part of routine antenatal care. 1,23 This study found a 34-day median delay between diagnosis and registration into care among pregnant women; nonetheless, within the limited and critical time frame of a pregnancy, even this comparatively small delay may have implications for missed opportunities for preventing mother-to-child transmission, especially among women presenting late to antenatal care. However, in 2007, as many as 99% of Ukrainian women received at least one antenatal care visit.…”
Section: Discussionmentioning
confidence: 78%
“…The right to health includes freedom from involuntary medical treatment, which links closely to consent to HIV testing and immediate treatment. Consent to testing and treatment must be safe guarded even in light of the need to test a large proportion of the population for a population wide treatment as prevention intervention to work . Essential safeguards should include on‐going and continuous training of health workers, monitoring of testing and consent, and information to the community about possible implications of an HIV test and life‐long treatment.…”
Section: Analysis – Key Human Rights Principles and Their Applicationmentioning
confidence: 99%
“…Consent to testing and treatment must be safe guarded even in light of the need to test a large proportion of the population for a population wide treatment as prevention intervention to work. 55 Essential safeguards should include on-going and continuous training of health workers, monitoring of testing and consent, and information to the community about possible implications of an HIV test and life-long treatment. For this, services will need to be sufficiently resourced with oversight and redress mechanisms in place.…”
Section: Accountabilitymentioning
confidence: 99%